Does Sharia Intellectual Capital Enhance the Share Prices of Mining Sector Companies Listed on the Indonesian Sharia Stock Index? - Melvia , Efta; Eliza , Any; Ermawati , Liya (Tazkia Islamic University College, 2023)
This study aims to examine the effect of sharia intellectual capital on the stock prices of mining sector companies listed on the Indonesian Sharia Stock Index (ISSI). Value-added human capital, structural capital value-added, and value-added customer capital are used as indicators to measure Islamic intellectual capital. This study uses a quantitative approach. The type of data used is secondary data in the form of annual reports and audited financial statements of mining companies for the 2016-2020 period. By using a purposive sampling technique, 85 samples were selected from the total financial statements of all mining sector companies. The documentation method is used as the main data collection technique in this study. The data analysis technique used multiple linear regression analysis. The results of multiple linear regression analysis show that value-added human capital and structural capital value added partially have a significant effect on sharia stock prices, while value-added customer capital has no significant effect on sharia stock prices.